TINDAK PIDANA PEMILU DI INDONESIA - La Ode Hamzah; Ali Rizky; Kamaruddin (Journal Publicuho, 2023)
The purpose of this writing is to determine the influence of political power and political fraud on law enforcement in Indonesia during the general election. This research uses normative legal research methods. Normative research is research carried out by examining library materials. The data used in this research is secondary data which includes primary and secondary legal materials. Data collection was carried out using the literature study method, namely by collecting, reviewing and processing literature, statutory regulations and articles, journals and scientific works. The results of the analysis are then described in sentence form systematically to make it easier to draw conclusions from the data. The research results show that the influence of political power and political fraud on law enforcement in Indonesia has negative impacts such as inequality before the law, decreased credibility of the legal system, disruption of the legal policy-making process, decreased legal quality, and increased legal uncertainty. These impacts threaten the stability and development of the country and hinder fair law enforcement.